Rekontruksi Kinerja Pendidikan NU di Era Global Perspektif Profetik - Moh Roqib (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2016)
Abstract: Nahdlatul Ulama or NU Is an organization with the largest number of members in the world. It's has unique management, with very diverse human resources. HR diversity is a huge treasure if properly managed, with programs and effect that is very useful for the people. It is necessary for the reconstruction of the performance that the is more powerful and useful. NU education has strategic position as an alternative educational institution, participatory, complementary. NU Education also offers a friendly face of Islam, as brought by the scholars have breadth of knowledge and science interwoven sanad continued from teacher teacher came to the Prophet Muhammad. In accordance with the Prophet who was sent to all the people who rahmatanlil â€˜alamin, in this era of globalization NU education needs to be reconstructed in accordance with the prophetic role. This reconstruction is to assert ulamaâ€™ role again, raise awareness for education managers and citizens, optimizing Education Provider (BPP) or LP2 Maarif NU-MNU, mapping community's needs and potentials, forming a team implementing educational operations related to all aspects of community life, develop scholarship agencies, build team cohesiveness labor, help each other and expanding networks, and create institutions â€œpilot studyâ€ integrative inclusive international standard. Keywords: Reconstruction, Performance, NU's Education, Prophetic Perspective